2019
DOI: 10.1001/jamanetworkopen.2019.2843
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Fetal and Infant Weight Change With General, Visceral, and Organ Adiposity at School Age

Abstract: Importance Both fetal and infant growth influence obesity later in life. The association of longitudinal fetal and infant growth patterns with organ fat is unknown. Objective To examine the associations of fetal and infant weight change with general, visceral, and organ adiposity at school age. Design, Setting, and Participants This cohort study was embedded in the Generation R Study, a population-based prospective cohort study in Rotterdam, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 44 publications
2
60
1
1
Order By: Relevance
“…Our findings differ from three studies from the "Generation R" cohort, which did observe interaction effects between infant weight gain and patterns of fetal weight gain (Gishti et al 2014;Toemen et al 2016;Vogelezang et al 2019). However, across the three studies, the interaction effects differed depending on the outcome.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our findings differ from three studies from the "Generation R" cohort, which did observe interaction effects between infant weight gain and patterns of fetal weight gain (Gishti et al 2014;Toemen et al 2016;Vogelezang et al 2019). However, across the three studies, the interaction effects differed depending on the outcome.…”
Section: Discussioncontrasting
confidence: 99%
“…Conversely, children who had "decelerated growth" during both gestation and infancy had a larger left ventricular mass (Toemen et al 2016). Finally, in the third study, Vogelezang et al (2019) observed that children who had either fetal growth deceleration or acceleration followed by accelerated infant growth displayed suboptimal adiposity profiles in childhood. As such, the overall conclusion from these studies is unclear.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…chronic noncommunicable diseases in the short-and medium-term and is additionally related to school-age adiposity [33]. In our neonates, AC was moderately correlated with an increase in their mothers' gestational weight (r = 0.45, p = 0.016), but not with P-BMI.…”
Section: Plos Onementioning
confidence: 46%
“…Moreover, it has been proposed that both nutrient overabundance and scarcity during pregnancy and infancy lead to a metabolic programming that results in an increased obesity risk throughout the lifespan (40). In fact, in a longitudinal cohort in Rotterdam, individuals with fetal growth restriction followed by infant weight acceleration had higher visceral and liver adiposity than those with normal fetal and infant growth (41).…”
Section: Gestational Age Birthweight Breastfeeding and Complementamentioning
confidence: 99%